A Juridical Review of Cikibul Snacks Seen from the Regulation of the Ministry of Health KL.02.02/C/90/2023 concerning Supervision of the Use of Liquid Nitrogen in Ready-to-Eat Food Products - Istikomah, Umi; Marlina, Tina; Maulinda, Irma (Jurnal Legisci, 2024)
A case of reporting concerning snack food consumption that uses liquid nitrogen occurred in Ponorogo, Tasikmalaya, Jakarta. The first case occurred with 1 case in children in Ponorogo Regency, which caused burns. The second case occurred in 23 people in Tasikmalaya Regency, which caused KLB to suffer from food poisoning. The third case occurred in a 4.2-year-old boy in Jakarta who caused severe abdominal pain. This study aims to find out and analyze the role of the Cirebon City Health Office in supervising cikibul food. To find out and analyze the efforts and obstacles experienced by the Cirebon City Health Office. The method used in this study is empirical juridical research, which is legal research that examines how law is applied in society and its impact. Empirical law research is carried out from an empirical point of view. Supervision by the Cirebon City Health Office has been carried out with applicable or operational standards of appropriate procedures. However, the results have not been maximized, as several traders are still selling cikibul. The efforts and obstacles faced by the Cirebon City Health Office in supervising the use of liquid nitrogen are to form a team and inspect locations that are suspected to be placed to sell Kabul. The obstacle is that when conducting the inspection, no cikibul sellers were found, the information that will be carried out is already known, some stubborn traders continue to peddle cikibul in a hidden way, and the location is far away.